The Environmental Effects of Lead Concentrations on Protein and DNA Structures in Epileptic Patients from an Infrared Spectroscopic Study - Jane Anastassopoulou; Maria Kyriakidou; Pavlos Nisianakis; George Papatheodorou; Michail Rallis; Theophile Theophanides (Journal of Basic & Applied Sciences, 2019)
Fourier transform infrared (FT-IR) and inductively coupled plasma mass spectrometry (ICP-MS) elementary analysis were used to investigate the environmental effects of lead blood serum levels on the life metal ions (Cu2+ and Zn2+), protein secondary structure and DNA structure in epileptic patients. By increasing the lead concentration an increased intensity of the band at 1744 cm-1 was observed due to induced oxidative stress. The shifts of the amide I and amide II bands of the peptide group, -CONH- from 1655 cm-1 and 1550 cm-1, respectively, to lower frequencies is due to the change of protein molecular structure from α-helix to β-sheets. An important change in the spectral region between 1200-900 cm-1, where the phosphates and phosphate-ribose groups of DNA and RNA are absorbing, is suggesting an attack on the DNA backbone as a function of the increase of lead concentration. The characteristic band at 1170 cm-1 could be used as a “marker band” for the damaged DNA backbone structure upon lead exposure. The ICP-MS elementary analysis showed a decrease of the ratio [Cu/Zn] by increasing the lead levels in blood serum is linked to oxidative stress and is confirming the FT-IR data.